1991
DOI: 10.1002/1097-4679(199111)47:6<846::aid-jclp2270470616>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics common to females who exhibit anorexic or bulimic behavior: A review of current literature

Abstract: This paper reviews recent literature on the characteristics of females who exhibit anorexic or bulimic symptoms. Although researchers categorize bulimics as either binge/restrictors or binge/purgers, this paper does not distinguish between the two with regard to characteristics. Personal, cognitive, and physical characteristics, as well as external influences, are examined for each. An additional purpose of the paper is to provide an overview of risk factors that may predispose an individual to bulimia nervosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…This same pattern of comorbidity has been reported in females with eating disorders (10,11,20), although the high proportion of substance abuse among our bulimic males (61%) is higher than comparable estimates in bulimic females, a difference that may reflect the higher prevalence of substance abuse among males in the general population (DSM-IV). The high prevalence of family psychopathology in our study group is also similar to published figures for females with eating disorders (21). While information on outcome was limited by the nature of the retrospective design, we found that over one-half of the 54 men for whom we had such data were doing poorly at 1-year follow-up; similar outcome figures have been reported for women with eating disorders (22).…”
Section: Discussionsupporting
confidence: 88%
“…This same pattern of comorbidity has been reported in females with eating disorders (10,11,20), although the high proportion of substance abuse among our bulimic males (61%) is higher than comparable estimates in bulimic females, a difference that may reflect the higher prevalence of substance abuse among males in the general population (DSM-IV). The high prevalence of family psychopathology in our study group is also similar to published figures for females with eating disorders (21). While information on outcome was limited by the nature of the retrospective design, we found that over one-half of the 54 men for whom we had such data were doing poorly at 1-year follow-up; similar outcome figures have been reported for women with eating disorders (22).…”
Section: Discussionsupporting
confidence: 88%
“…16 21 26 31 36 41 46 51 56 61 66 71 76 81 86 Case number Difference in onset of eating disorder and IBS Fig. 1.…”
mentioning
confidence: 99%
“…For other bulimics, there may be other etiological factors involved in the maintenance of both dissociative and bulimic behaviors. In particular, bulimic behaviors themselves are profound physiological stressors which often coexist with psychological symptoms such as depression (Schumaker et al, 1995;Zerbe et al 1993) and anxiety (Kerr, Skok, & McLaughlin, 1991). Demitrack et al (1990) have proposed that these behaviors may "alter the individual's conscious state or alternatively serve as contextual cues for the induction of dissociative states and in so doing perpetuate or enhance the propensity of the patient to dissociate" (p. 1187).…”
Section: Discussionmentioning
confidence: 99%